Using formal and informal formative assessment to support bilingual argument mapping in university bilingual science courses. Issue 9 (21st October 2022) - Archila, Pablo Antonio; Gravier, Gissel; Levy, Laura; Ortiz, Brigithe Tatiana; Rodríguez, Alejandra; Wilches, Luciana; Truscott de Mejía, Anne-Marie; Restrepo, Silvia
ABSTRACT : The rise in university bilingual science courses is explained by a certain phenomenon, the internationalization of higher education. Bilingual Argument Mapping (BAM) – the ability to construct argument maps using two languages – is a key aspect of bilingual scientific literacy. An argument map is a visual representation of argument structure. The problem is that little is known about how to foster BAM in this type of course. The goal of this study was to explore the possibility of using formal and informal formative assessment (FIFA) – a type of assessment for learning in which feedback is both preplanned and instantaneous –, to support undergraduates' BAM. The data consist of the bilingual argument maps constructed by forty-four students (27 females and 17 males, 18–23 years old) in Colombia during a university Spanish-English bilingual science course. Results indicate that FIFA helped the participants' creation of valid and coherent argument maps in Spanish, in English and in a hybrid version using code-switching as response to argumentative questions related to the scientific topics covered in the course. The potential contributions of FIFA and its implications are discussed in light of research and theory of bilingual science education.